Some Difficulties Faced by Grade Seven Students of MTS. Al-Haq Palu in Writing Descriptive Text: Kesulitan yang Dihadapi Ooeh Siswa Kelas Tujuh di MTS. Al-Haq Palu dalam Menulis Deskriptif Teks - Nursakinah; Nadrun; Budi (Jurnal Kolaboratif Sains, 2022)
The purpose of this research is to investigate the writing problems faced by grade seven students of MTs. Al-Haq Palu. This research applied descriptive method. The subject was grade seven students of MTs. Al-Haq Palu, with 21 students taken from one class by using total sampling technique. The data of the research were collected by carrying out the test, interview, and questionnaire. The result of this research indicates that the students faced many problems which include (1) they were lack of vocabulary; (2) they got difficulty to explore their ideas; (3) they could not choose appropriate words; and (4) they could not use spelling and punctuation well.